Soil acidification and nutrient imbalance mediate fungal community degradation, a key driver of continuous cropping obstacles in Platycodon grandiflorus - Li, Li; Yang, Hao; Peng, Dian; Liu, Ruibo (Frontiers in Microbiology, 2025)
IntroductionContinuous cropping obstacles severely restrict the sustainable cultivation of Platycodon grandiflorus. This study aimed to clarify the key drivers underlying these obstacles, focusing on the roles of soil physicochemical properties and rhizosphere fungal community dynamics.MethodsThis study analyzed the growth indicators of Platycodon grandiflorus, soil physicochemical properties, and the characteristics and functions of fungal communities under different durations of continuous cropping years.ResultsContinuous cropping significantly inhibited the growth of Platycodon grandiflorus. As the continuous cropping years continued, root length, root diameter, yield, and alcohol-soluble extract content decreased, the abundance of Fusarium increased, and root rot was exacerbated. Continuous cropping led to soil acidification, reduced phosphorus and potassium contents, and an imbalance of the fungal community; the abundance of acid-tolerant pathogens increased while beneficial fungi decreased in abundance, with pathotrophic and saprotrophic fungi enriched, resulting in slowed soil carbon turnover and reduced disease resistance.DiscussionOur findings demonstrate soil acidification and phosphorus/potassium depletion mediate fungal community degradation. Adjusting soil pH, supplementing phosphorus/potassium, and inoculating functional fungi may alleviate obstacles, providing empirical support for sustainable Platycodon grandiflorus cultivation